2011
DOI: 10.1097/ta.0b013e31823ac642
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interhospital Transfer on Outcomes for Trauma Patients: A Systematic Review

Abstract: Available evidence suggests there is no difference in mortality between transfer and direct admissions. However, the significant heterogeneity across studies precludes deriving any definitive conclusions regarding the impact of interhospital transfer on mortality after major trauma. Moreover, most studies excluded patients dying at outlying hospitals, which may underestimate the association of transfer status with mortality. Prospective studies that address the limitations of the current evidence, including us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 54 publications
(189 reference statements)
4
85
1
Order By: Relevance
“…In their consensus report, the authors specify that EMS is a “critical infrastructure requirement to ensure timely, reliable and appropriate transportation of the acute MI patient” and that “improvements in both the interfaciity transfers and repatriation process would be required.”31 No one entity is responsible for the FMC2B time, since it involves multiple time intervals, reliant on a coordinated system of care. In regional systems of care, awaiting a transport resource can result in unacceptable delays for time‐critical emergencies 32, 33. The mortality benefit of transfer for PPCI compared with fibrinolysis is limited to 120 minutes, and delays in transport can result in an inability to provide this preferred treatment within the recommended timeframe.…”
Section: Discussionmentioning
confidence: 99%
“…In their consensus report, the authors specify that EMS is a “critical infrastructure requirement to ensure timely, reliable and appropriate transportation of the acute MI patient” and that “improvements in both the interfaciity transfers and repatriation process would be required.”31 No one entity is responsible for the FMC2B time, since it involves multiple time intervals, reliant on a coordinated system of care. In regional systems of care, awaiting a transport resource can result in unacceptable delays for time‐critical emergencies 32, 33. The mortality benefit of transfer for PPCI compared with fibrinolysis is limited to 120 minutes, and delays in transport can result in an inability to provide this preferred treatment within the recommended timeframe.…”
Section: Discussionmentioning
confidence: 99%
“…This event is quite frequent, accounting for at least a third of patients admitted to Level I or II TCs. 4 It is also reported that as many as a third of severely injured patients initially evaluated at these nontrauma centers (NTCs) are never transferred. 5,6 There is substantial variability in rates of interfacility transfer after trauma, suggesting that factors other than those related to patient needs might be at play.…”
mentioning
confidence: 99%
“…Total costs for transferred patients were higher, and these patients had longer hospital stay than direct admits. 36 Many patients who are victims of major trauma are taken to trauma centers via rotary-wing transport. The nature of their injuries and the environment within the aircraft, which is noisy and cramped, may increase the chance of AEs.…”
Section: Transport Of Trauma Patientsmentioning
confidence: 99%